LGBTQ+ persecution during the Holocaust : an encyclopedia of prejudice and perseverance - Herr, Alexis (2025)
"Gives voice to the experiences of LGBTQ+ persons prior to, during, and after the Holocaust, showing how the Nazi regime instituted a violent, oppressive, and murderous attack on LGBTQ+ life, culture, and identity"-- Provided by publisher.
Includes bibliographical references.
Keywords: Gay people -- Germany -- Social conditions -- 20th century; Gay people -- Nazi persecution -- Germany; National socialism and homosexuality; Holocaust, Jewish (1939-1945) -- Germany; Homosexuality -- Germany -- History -- 20th century; Encyclopedias